Virtual Reality for Architectural or Territorial Representations: Usability Perceptions - Atta Idrawani Zaini; Mohamed Rashid Embi (International Journal of Built Environment and Sustainability, 2017)
Virtual reality (VR) is widely being researched within various aspects of real-world applications. As architecture and urban design are very much adhered to evaluating and designing space, physical representations are deemed as incompetent to deliver a full-scale depiction of a space. Similarly, digital models are very much also limited in that sense. VR can deliver a full-scale virtual environment (VE), tricking users to be immersed in the replicated environment. This is an advantage for the aforementioned design disciplines, as more relatable and realistic depiction of a space can be modelled. The notion of its usability has become important to be understood from the perspective of architecture and urban design. This paper measured the respondents’ perceptions of VR’s usability through measuring its quality of use based on several criteria. The criteria established were the ease of use, usefulness, and satisfaction. Different levels of architectural details were decided as a form of control. A total of N=96 randomly selected respondents from various backgrounds participated in the survey as they were divided into four different group of treatments. Each group experienced a different VE with different level of architectural details. The first section of analysis is a one-sample analysis and the second is a group difference analysis. From the first analysis, it was found that the respondents perceived VR as a usable tool for architectural or territorial representation. Using Kruskal-Wallis test, it was found that there was no statistically significant difference between groups, suggesting that the respondents perceived VR as usable regardless of the level of architectural details. As this paper used perception data based on the quality of use alone, the efficiency of VR system was not measured. Thus, this paper recommends further studies to be conducted on the system’s efficiency to reflect its usability in full extent.